Rheological And Physicochemical Properties Of Pasteurized And Sterilized Bambangan (Mangifera Pajang) Fruit Puree - Rivoldiantoe, N.N.; Hay, C.L.; Ab Wahab, N.; Abdul Aziz, A.H.; Mamat, H.; Saalah, S.; Ismail, N.M.; Chiam, C.K.; Saallah, S.; Bahauddin, A.R.; Roslan, J. (2026)
Indexed by Scopus/MyCite